Generated four-wave mixing in temperature controlled mixtures of carbon disulfide and benzene. (20th October 2022) - Li, Shuang; Liang, Han; Liu, Xiaofeng; Fang, Wenhui; Sun, Chenglin; Men, Zhiwei
Abstract: Generated four-wave mixing (FWM) from the Cascaded stimulated Raman scattering (SRS) process of the mixtures of carbon disulfide and benzene on temperature was investigated. At the low temperature conditions, the stimulated Brillouin scattering can be significantly suppressed, the beam distortion caused by thermal self-defocusing effect can be reduced, thereby improving the energy conversion efficiency of SRS. Not only the multi-order Stokes and anti-Stokes SRS of CS stretching vibration, CC ring skeleton vibration and CH stretching vibration were obtained, but also the 1st (∼583 nm) and 2nd -order (∼646 nm) FWM was generated by the Stokes light, anti-Stokes light and pump laser. At 20 °C, the highest conversion efficiency is 32%, and the peak intensity of FWM is also the intensest. The results are of great significance for the multi-wavelength Raman laser in liquid medium.